EFFICIENCY OF MICRONIZED PROGESTERONE IN PREGNANT WOMEN AT RISK OF SPONTANEOUS ABORTION (Journal of Science-Innovative Research in Uzbekistan, 2024)
Below we would like to clarify the issues that arise in practice in patients who are prescribed micronized progesterone in obstetrics and gynecology.Micronized progesterone has been widely used over the past 40 years in different countries of the world as the main factor of preserving the fetus in early and late pregnancy. The risk of miscarriage is one of urgent problems that are growing day by day. Planning the first pregnancy after 30-35 years, an increase in number of pregnancies after assisted reproductive technologies, the negative impact of environmental factors, stress - all these factors increase the complication of pregnancy and, first of all, the number of spontaneous abortions.